A Gas‐Sensitive SPIM Sensor for Detection of Ethanol Using SnO2 as Sensing Element. Issue 12 (6th March 2019) - Wang, Mengyun; Truong, Hoang A.; Werner, Carl F.; Miyamoto, Ko‐ichiro; Yoshinobu, Tatsuo
Abstract : In this study, a gas‐sensitive scanning photo‐induced impedance microscopy (SPIM) sensor using tin dioxide (SnO2 ) as sensing element is proposed, which detects the local impedance change on the sensor surface in response to ethanol vapor. The impedance change of the SnO2 film is detected by monitoring the AC photocurrent signal induced by a laser beam. This measurement can be done in a spatially resolved manner by using a scanning laser beam and two‐dimensional maps are obtained thanks to the light‐addressability of SPIM. This technique is expected to be applied to the visualization of gas distributions on the sensing surface. Abstract : A gas‐sensitive scanning photo‐induced impedance microscopy (SPIM) sensor using tin dioxide (SnO2 ) as sensing element is proposed, which detects the local impedance change on the sensor surface in response to ethanol vapor. Thanks to the light‐addressability of SPIM, two‐dimensional maps are obtained by using a scanning laser beam, which can be applied to the visualization of gas‐concentration distributions on the sensing surface.